Uczenie się jako przestrzeń dyskursywnie konstruowana - Popow, Monika (Kultura-Społeczeństwo-Edukacja, 2019)
The aim of this paper is to present the conception of learning as a discursive space. It presents the existing research in the field of critical discourse theory, cultural processes of learning as well as dialogic theory of learning. Different aspects of discourse of learning are discussed, including learning as a space for identity creation processes. Furthermore the issues of empty signifiers in a discourse of learning as well as cultural aspects of the discourse of learning and its consequences for identity creation processes are raised.